Health Information and Advertising Appeals in Food Commercials: A Content Analysis - Chan, Kara; Leung, Vivienne; Tsang, Lennon (Journal of Nutritional Therapeutics, 2013)
A content analysis of 311 food commercials broadcast on television networks in Hong Kong was conducted. There were nearly equal proportions of ads for healthy and unhealthy foods. The three most frequently used advertising appeals were taste/flavor/smell/texture, health/wellbeing and physical performance/speed/strength. Altogether 54 percent of the food ads contained health-related claims. Intriguingly, 23 percent of the ads for unhealthy food contained health-related claims. The prevalent use of general health claims in unhealthy food ads calls for policy makers to devise better ways to regulate health claims in food advertisements. This is the first content analysis of health and nutrition information in food advertising arising from a society with a rich herbalist tradition.